Search for Higgs boson pair production in the [Formula: see text] final state from pp collisions at [Formula: see text] TeVwith the ATLAS detector - Aad, G; Abbott, B; Abdallah, J; Abdinov, O; Aben, R; Abolins, M; AbouZeid, O S; Abramowicz, H; Abreu, H; Abreu, R; Abulaiti, Y; Acharya, B S; et al. (The European physical journal. C, Particles and fields, 2015)
A search for Higgs boson pair production [Formula: see text] is performed with 19.5 fb[Formula: see text] of proton-proton collision data at [Formula: see text] TeV, which were recorded by the ATLAS detector at the Large Hadron Collider in 2012. The decay products of each Higgs boson are reconstructed as a high-momentum [Formula: see text] system with either a pair of small-radius jets or a single large-radius jet, the latter exploiting jet substructure techniques and associated b-tagged track-jets. No evidence for resonant or non-resonant Higgs boson pair production is observed. The data are interpreted in the context of the Randall-Sundrum model with a warped extra dimension as well as the two-Higgs-doublet model. An upper limit on the cross-section for [Formula: see text] of 3.2 (2.3) fb is set for a Kaluza-Klein graviton [Formula: see text] mass of 1.0 (1.5) TeV, at the 95 % confidence level. The search for non-resonant Standard Model hh production sets an observed 95 % confidence level upper limit on the production cross-section [Formula: see text] of 202 fb, compared to a Standard Model prediction of [Formula: see text] fb.